VALUATION OF TECHNOLOGICAL FEATURES OF TOBACCO SEED CULTIVATION IN UKRAINE AND ITS ECONOMIC EFFICIENCY - Hanna BIALKOVSKA; Anatoliy YURECHKO; Volodymyr PASHCHENKO (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The article provides a valuation of the technological features of cultivating new perspective varieties of Ukrainian selection tobacco seeds, which have high resistance to biotic and abiotic factors, good raw material quality, and optimal levels of nicotine, carbohydrates, and proteins. The scientific principles of cultivation and realization of high productive, competitive tobacco varieties, such as Berley 38, Berley 46, Ternopil 14, and Ternopil Perspective, are substantiated. The economic efficiency of tobacco seed production for Ukrainian research institutions is determined. Only specialized research institutions with corresponding scientific potential and material-technical base should be engaged in tobacco seed cultivation and realization. The production of tobacco seed varieties with optimal chemical composition will increase the efficiency of tobacco production and competitiveness of national seed production.